Hammīra: chapters in imagination, time, history - Malik, Aditya (De Gruyter, 2021)
Frontmatter -- Preface -- Contents -- Acknowledgments -- Prologue -- Chapter 1 Historical Contexts -- Chapter 2 Singular Moments -- Chapter 3 Realms of Imagination -- Chapter 4 Literary Imbroglios -- Chapter 5 The Poet’s Dream -- Chapter 6 History as Simulacrum -- Chapter 7 Interiors of the Past -- Epilogue -- Appendix 1 -- Appendix 2: Conversations at Ranthambore -- Bibliography -- Authors -- Subjects
Keywords: Fiktionale Darstellung; Geschichte; Legende; Mythos; Religiöse Bewegung; Rajasthan; Geschichte 1400-1600; König; Epos; Sanskrit; Hammira <Mewar, Mahārāṇā>